Engineering plasmonic semiconductors for enhanced photocatalysis. Issue 35 (9th August 2021) - Li, Juan; Lou, Zaizhu; Li, Baojun
Abstract : This perspective provides an outlook on the advancing research regarding on strategies to engineer plasmonic semiconductors for enhanced photocatalysis. Abstract : Localized surface plasmon resonance (LSPR) is an intriguing phenomenon induced by the collective oscillations of free carriers with incident light, and has attracted considerable interest for the plasmon-enhanced photocatalysis. Since the first report of plasmonic photocatalysis in 2009, various materials of metals/semiconductors, bimetals and semiconductors have been reported as active plasmonic photocatalysts. With low-cost and abundant reserves, plasmonic semiconductors are promising candidates for photocatalysis as substitutes for high-cost and rare noble metals. Various plasmonic semiconductors have been explored for photocatalytic chemical reactions such as hydrogen generation, CO2 reduction, and organic synthesis because of the strong LSPR in visible and near-infrared (Vis-NIR) regions. Moreover, plasmonic semiconductors with both electronic structures of the intrinsic band and LSPR property allow for broad absorption in the UV-Vis-NIR region and are ideal materials for solar energy conversion. However, there still remain obscure problems such as differences between plasmonic semiconductors and metals, LSPR-mediated photochemical and physical processes, as well as a detailed mechanism of LSPR-enhanced photocatalysis over plasmonic semiconductors. In this perspective, we summarize the recent development of plasmonic semiconductors and their promising applicability in photocatalysis. We also highlight and provide an outlook on the advancing research regarding strategies to construct LSPR on semiconductors for high-efficient photocatalysis, including (1) decreasing the thickness of depletion layers, (2) constructing plasmonic p–n heterostructures, (3) anisotropic LSPR on semiconductors and (4) mechanism study on p-type plasmonic semiconductor for photocatalysis.